TINDAK PIDANA PENGANIAYAAN YANG MENGAKIBATKAN MATINYA SESEORANG (Studi Kasus di Pengadilan Negeri Denpasar) - Agus Gauthama Putra, I Putu; Rai Setiabudhi, I Ketut; Parwata, I Gusti Ngurah (Kertha Wicara : Journal Ilmu Hukum, 2013)
Maltreatment resulting in death of person is an act in which the form of the attack on the body or parts of the body that cause pain or injury, even to the causing of that. Over of that, while the problems faced by the application of criminal how that can be imposed against the perpetrators of abuse and what is the basis for consideration of the judge in imposing maltreatment resulting in death of person. Purpose of this study is generally an attempt to fit the development of legal science of changing times and never reached the point of final. This research method is used descriptive. The result of this study is statement in the trial judge can be free from criminal prosecution or any claim under section 1 point 11 code of Criminal Procedure and the considerations are juridical and non juridical. Based on it can be concluded that maltreatment resulting in death of person can be imprisoned for 5 until 7 years in jail.
Keywords: Criminalization, Persecution, Consideration of Judge